2004
DOI: 10.1111/j.0022-1112.2004.00575.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of electrofishing and trammel netting variability for sampling native fishes

Abstract: The variability in size structure and relative abundance (CPUE; number of fish !200 mm total length, L T , collected per hour of electrofishing or trammel netting) of three native Colorado River fishes, the endangered humpback chub Gila cypha, flannelmouth sucker Catostomus latipinnus and bluehead sucker Catostomus discobolus, collected from electrofishing and trammel nets was assessed to determine which gear was most appropriate to detect trends in relative abundance of adult fishes. Coefficient of variation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 20 publications
0
17
0
Order By: Relevance
“…A gear-specific effect on detection probabilities was apparent for juvenile and adult burbot for both seasons. The effect of gear on detection probabilities was not surprising given the long-established biases associated with different fish sampling techniques (Paukert 2004;Hetrick & Bromaghin 2010). For instance, Schloesser et al (2012) reported that detection probabilities for a number of Missouri River fishes were most influenced by sampling technique (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…A gear-specific effect on detection probabilities was apparent for juvenile and adult burbot for both seasons. The effect of gear on detection probabilities was not surprising given the long-established biases associated with different fish sampling techniques (Paukert 2004;Hetrick & Bromaghin 2010). For instance, Schloesser et al (2012) reported that detection probabilities for a number of Missouri River fishes were most influenced by sampling technique (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…For example, relative abundance (e.g., catch-per-unit-effort; CPUE) and size structure (e.g., proportional size distribution; PSD) estimates often vary seasonally Willis 1991, Pope and due to factors such as behavior (e.g., spawning) and growth of individuals throughout the year. Additionally, different sampling gears often capture individuals of different numbers and sizes of the same species (Guy et al 1996, Tate et al 2003, Paukert 2004. Similarly, differences in gear specifications (e.g., dimensions and mesh size) and materials (e.g., filament type, color) used to construct sampling gear can bias estimates, such as relative abundance, size structure, and species composition (Willis et al 1984, Henderson and Nepszy 1992, Gray et al 2005, Wanner et al 2010.…”
Section: Introductionmentioning
confidence: 99%
“…Fisheries managers and researchers require unbiased estimates of fish population characteristics. Sampling techniques should provide a measure of relative abundance, and the fish captured should accurately reflect the size structure of the fish population (Guy et al., 1996; Colvin, 2002; Paukert, 2004). Sampling must also be standardized to obtain precise, unbiased estimates of fish population size and age structure and relative abundance (Allen et al., 1999).…”
Section: Introductionmentioning
confidence: 99%